Prodigy Finance - Bourg-Meyer, Vero; Gimeno, Javier; Elias, Jaan; Ederer, Florian (London : Yale School of Management, 2018)
As Prodigy Finance closed a $240 million fundraise in August 2017, the no-cosign, no-collateral financial services firm was seeking new ways to expand its business. Over the past ten years, it had focused on providing loans to international students at elite business schools who had no assets or credit history. In particular, Prodigy had enjoyed tremendous growth since a partnership with Credit Suisse in 2014 to set up the world's first "higher education note." But along with diversification, came the risk of losing what made Prodigy special in the eyes of its stakeholders. How should Prodigy make itself known to customers and investors? How should the company measure its success? How could the company maintain its community model as it rapidly expanded its financial base and regions served? Having made headway in the world of business schools, Prodigy had dipped its toes into new student pools like engineering, law, and policy. But these forays raised questions about whether Prodigy's model would work with students in other disciplines or countries. Should Prodigy serve these markets or even consider other groups of international students? Having pioneered a successful financing model, Prodigy also was considering other financial services that could make use of the company's risk model. What new products could Prodigy offer to support its student borrowers? What strategy should guide the company's new product development? Or should the company stick to the educational loans it pioneered and knew best?
Originally Published InBourg-Meyer, V., Gimeno, J., Elias, J., & Ederer, F. (2018). Prodigy Finance. Yale SOM Case 102-17. New Haven, CT: Yale School of Management, Yale University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Prodigy Finance; Strategic planning; Bank loans; Student loans; Student loan funds